PHYSICS EXPERIMENTS USING CALORIMETER PROTOTYPE - (NIM 20207042), NURDIN
Physics, which is one of basic sciences, needs a proof for its laws. The proof may be done by use of method of experiment. Some equipments are required to do an experiment. To support a learning-teaching process concerning heat, a simple equipment like calorimeter prototype is made. Calorimeter is tested after preparing an instructional guide of experiment. It covers several experiments such as experiments to determine the specific heat of various metals, the heat capacity of calorimeter, the heat absorbed by calorimeter, the electrical energy released into calorimeter, and the equivalence of heat and electrical energy. Analysis of measurement data results in the specific heat of various metals with error tolerance less than 20.7 % compared to those of literature and the heat equivalence with error tolerance less than 6.7%. It is concluded that the calorimeter prototype is feasible enough to use in supporting a learning-teaching process conceruing heat.